Influenza A virus NS1 protein represses antiviral immune response by hijacking NF-κB to mediate transcription of type III IFN - Lee, Meng-Chang; Yu, Cheng-Ping; Chen, Xing-Hong; Liu, Ming-Tsan; Yang, Ji-Rong; Chen, An-Yu; Huang, Chih-Heng (Frontiers in Cellular and Infection Microbiology, 2022)
Background Non-structural protein 1 (NS1), one of the viral proteins of influenza A viruses (IAVs), plays a crucial role in evading host antiviral immune response. It is known that the IAV NS1 protein regulates the antiviral genes response mainly through several different molecular mechanisms in cytoplasm. Current evidence suggests that NS1 represses the transcription of IFNB1 gene by inhibiting the recruitment of Pol II to its exons and promoters in infected cells. However, IAV NS1 whether can utilize a common mechanism to antagonize antiviral response by interacting with cellular DNA and immune-related transcription factors in the nucleus, is not yet clear. Methods Chromatin immunoprecipitation and sequencing (ChIP-seq) was used to determine genome-wide transcriptional DNA-binding sites for NS1 and NF-κB in viral infection. Next, we used ChIP-reChIP, luciferase reporter assay and secreted embryonic alkaline phosphatase (SEAP) assay to provide information on the dynamic binding of NS1 and NF-κB to chromatin. RNA sequencing (RNA-seq) transcriptomic analyses were used to explore the critical role of NS1 and NF-κB in IAV infection as well as the detailed processes governing host antiviral response. Results Herein, NS1 was found to co-localize with NF-κB using ChIP-seq. ChIP-reChIP and luciferase reporter assay confirmed the co-localization of NS1 and NF-κB at type III IFN genes, such as IFNL1, IFNL2, and IFNL3. We discovered that NS1 disturbed binding manners of NF-κB to inhibit IFNL1 expression. NS1 hijacked NF-κB from a typical IFNL1 promoter to the exon-intron region of IFNL1 and decreased the enrichment of RNA polymerase II and H3K27ac, a chromatin accessibility marker, in the promoter region of IFNL1 during IAV infection, consequently reducing IFNL1 gene expression. NS1 deletion enhanced the enrichment of RNA polymerase II at the IFNL1 promoter and promoted its expression. Conclusion Overall, NS1 hijacked NF-κB to prevent its interaction with the IFNL1 promoter and restricted the open chromatin architecture of the promoter, thereby abating antiviral gene expression.